PROFITABILITY AND CONSTRAINTS OF IFAD/VCD RICE PROJECT AMONG SMALLHOLDER FARMERS IN NIGER STATE OF NIGERIA - Sanusi Mohammed Sadiq; P I Singh; M M Ahmad; B J Yunnusa; M S Egba (Agricultural Socio-Economics Journal, 2021)
Failure to sustain most of the rural poor and food security programmes in Nigeria after their life span is due to poor productivity of the capital investment of a project to generate a remunerative income to sustain a typical agrarian farming household in Nigeria. Thus, to critically investigate this hypothetical proposition, this research aimed at evaluating the viability of the IFAD rice project among the beneficiaries in Niger State of Nigeria. Undated data of the 2018 rainfed cropping season was elicited from 111 farmers through a multi-stage sampling technique and the information were collected viaa structured questionnaire complemented with an interview schedule. Both descriptive and inferential statistics were used to analyze the data collected. The empirical results showed that the rice project in the study area is likely not to be sustained after the stipulated time frame for the programme as inspite of the programme aim of doubling farmers’ income viz. value chain. The capital investment is not productive to sustain an average farming household composed of 8 persons having an operational holding of less than two hectares. Therefore, the study recommends provision of consumption credit in addition to the production credit advanced to the farmers in order to make the capital investment viable so that its turnover after each production season will be consistently re-invested into the rice project and possibility of a farmer taken-up additional activities along the chain, thus keeping the business going concern viable and sustainable.